Social Occupational Therapy, transgender and Queer Theory: (re) thinking normative conceptions based in gender and sexualities - Maximiano de Melo, Kesia Maria [UNESP] (Cuba Editora, 2016)
This article seeks to discuss my trans experiences along with their developments arising from the normative conceptions of gender and sexuality in which social life is organized. To mark the discussion around these experiences, I used as theoretical goal some concepts of the Queer Theory such as the post-structuralism strand that questions the essentialism of subject, the normative conception and the stiffening of identity experiences. Furthermore, I sought an interlocution with the discussions on the occupational social therapy performance, analyzing the dimension of the practice and theory in actions aiming citizenship access, without losing sight of the urgent historical and cultural social phenomena understanding. It's necessary to think about these practices without losing sight of the coordinating agent position of the subject to the social reality, from the mediation and expansion of new ways of doing, the denaturalization of marginalized experiences and mainly of social emancipation, always articulating the macro dimensions with micro dimensions, and the individual with the collective.
Keywords: Heteronormativity; Sexuality; Gender; Post-Structuralism